Povezava polimorfizma gena za citokrom P450 (CYP1A1) z dovzetnostjo za pljučnega raka pri Slovencih - Kopač, Matjaž (Medicinski razgledi, 1998)
Two polymorphic sites of the CYP1A1 gene, coding for cytochrome P4501 A1 enzyme, have been discovered so far. One involves the 7th exon of the coding region; a nucleotide change leads to amino acid replacement in the heme binding region of cytochrome P4501A1 (polymorphism IIeNal). Another site is inthe 3',-flanking region of the gene, and results in the presence of a new restriction site for the Msp I enzyme (polymorphism Msp I). This study investigated the role of both polymorphisms in the development of lung cancer caused by chemical carcinogenesis. We analysed 156 samples obtained from patients with lung cancer, and 102 samples from healthy individuals. The method I used was based on amplification of the polymorphic part of the gene by polymerase chain reaction. To detect the polymorphism Msp I the products ofreaction were analysed using the restriction and electrophoresis on agarose gel, while the presence of polymorphism Ile/Val was determined using specific primers. For the identification of the reaction product electrophoresis on agarose gel was employed. A statistically significant association between polymorphism Msp I and polymorphism Ile/Val was found in both lung cancer patients and healthy controls. There was no statistically significant difference in the incidence of both polymorphism forms between lung cancer patients and controls or between patients with different histological subtypesof lung cancer.
Keywords: Lung neoplasms; pljučni rak; novotvorbe; Genetics; tumor; genetika; Cytochrome p-450 cyp1a1; Polymorphism (genetics); Polymerase chain reaction